(untitled) (Journal of the College of Basic Education, 2022)
A survey of prevalence of intestinal parasites among the Erbil citizen was performed during the year of 2011. The setting is a community in endemic area of parasites infections without the recent previous history of antihelminthic drug distribution. Stool specimen examined for 1505 (992(65.9%) male and 513(34.1%) female) were performed for the period of 12 months (January to December) in the year 2011 in the Erbil province. A total of 1009 samples gave positive diagnoses of parasitic infection, including 494 (63.0%) males, 513 (62.2%) females’ patients. The common parasites found namely were Entamoeba histolytica, Giardia lambelia, Trichomons homins and Hymenolips. While the percentage of infection with those parasites within the positives cases were 776 (76.9%), 226(22.4 %), 6(0.6%), 1(0.1%) respectively during the year.